2019
DOI: 10.1111/acps.13004
|View full text |Cite
|
Sign up to set email alerts
|

General hospital admission rates in people diagnosed with personality disorder

Abstract: Objective To determine the frequency of all‐cause general hospital admissions for individuals with personality disorder (PD) in a large clinical population using linked secondary mental healthcare and hospitalisation data. Method A retrospective cohort study, using anonymised electronic mental health records from South London and Maudsley NHS Foundation Trust (SLaM), linked to Hospital Episodes Statistics in England. People with PD aged 15 years or older, receiving care within SLaM between April 2007 and March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 40 publications
0
23
1
Order By: Relevance
“…Unlike results of other studies [ 27 , 61 ], this study identified personality disorders, drug related disorders and suicidal behaviors as negative predictors of hospitalization among patients with moderate or frequent hospitalizations compared with no hospitalizations. This situation may be partially due to stigmatizing attitudes among hospital staff toward patients with personality disorders or drug related disorders, considering them less than optimal candidates for hospitalization [ 75 , 76 ].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Unlike results of other studies [ 27 , 61 ], this study identified personality disorders, drug related disorders and suicidal behaviors as negative predictors of hospitalization among patients with moderate or frequent hospitalizations compared with no hospitalizations. This situation may be partially due to stigmatizing attitudes among hospital staff toward patients with personality disorders or drug related disorders, considering them less than optimal candidates for hospitalization [ 75 , 76 ].…”
Section: Discussioncontrasting
confidence: 81%
“…Studies have examined risk factors for frequency of hospitalization in the general population [ 11 , 24 , 25 ]. The following needs factors were associated with high hospitalization rates: MD diagnoses [ 24 ], especially depressive symptoms [ 26 ] and personality disorders [ 27 ], co-occurring MD and physical illnesses [ 11 ], and co-occurring SUD and physical illnesses [ 25 ]. One study [ 24 ] found that older age (predisposing factors) and possession of health insurance (enabling factors) were linked to high hospitalization rates.…”
Section: Introductionmentioning
confidence: 99%
“…Large cohort studies indicate people diagnosed with a personality disorder have higher rates of conditions such as cardiovascular disease (Moran et al, 2007), arteriosclerosis, hepatic disease, hypertension, gastrointestinal disease and arthritis (El‐Gabalawy et al, 2010). One United Kingdom (UK) study found hospital admissions, related to circulatory, respiratory, digestive, musculoskeletal, nervous and endocrine systems were three times higher in people diagnosed with a personality disorder compared to the general population (Fok et al, 2019). Although, the retrospective cohort design used by Fok et al (2019) was reliant on the accuracy of National Health Service (NHS) records and did not address potentially confounding variables, such as lifestyle and psychiatric comorbidity; the study highlighted disparities that have to date, received very little attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the impressive sample, this remains the finding of a single study. Multiple explanations have been put forward for the decline in borderline personality disorders in older adults, such as high morbidity and mortality due to risk behavior, suicide and somatic comorbidity [23,24], and a decrease in impulsive and aggressive behavior when comes to age. For personality disorders in general, it has been demonstrated that 29% of the diagnostic criteria are not age neutral, which could lead to under detection of personality disorders in later life [25].…”
Section: Introductionmentioning
confidence: 99%